Effect of Hydroxyapatite Nanoparticles Addition on Water Sorption and Water Solubility of Heat-Cured Acrylic Resin Material - Saif Mohanad Al-Obaidy; Ammar Khalid Al-Noori (University of Mosul, College of Dentistry, 2024)
Aims: To investigate the effects of the incorporation of hydroxyapatite nanoparticles (HA NPs) with size (20 nm) at two concentrations (0.5% and 1%) on the water sorption and water solubility of heat-cured acrylic resin. Materials and methods: The total number of specimens was thirty which was divided into ten specimens (control, 0.5 % HA NPs, and 1 % HA NPs). The statistical analysis was done by using the SPSS program including descriptive statistics, ANOVA, and Duncan's test at p ≤ 0.05. Results: The results demonstrated that there was a significant decrease in the water solubility and a nonsignificant decrease in water sorption for the PMMA-HA nanocomposite at HA nanoparticles (0.5%) and (1%), when compared to control. Conclusions: the use of hydroxyapatite nanoparticles as dental fillers at 0.5% and 1% by weight decreased the water sorption and water solubility of PMMA denture base material.